Elevated liver enzymes and its association with uncontrolled type 2 diabetes mellitus: A study from South India - Avinash HR,; Naveen K Nandeppagoudar,; Mamatha TR,; Arpith AG, (Asian Journal of Medical Sciences, 2025)
Background: Diabetes mellitus is one of the most common chronic diseases has been related to various liver illnesses such as liver enzyme derangements, non-alcoholic fatty liver disease, hepatocellular carcinoma, and cirrhosis. There has been increased interest on the contribution of liver enzymes to prediction of diabetes and glycemic control. Aims and Objectives: The aim is study was to correlate liver enzymes with Hemoglobin A1c (HbA1C) in type 2 diabetes mellitus (T2DM) with uncontrolled sugars. Materials and Methods: Diabetic patients seen on Outpatient Department basis or admitted as inpatients are included in this study. Information is collected and detailed history is taken using pre-formed proforma at the time of admission. Liver function tests are measured to all participants, and HbA1C value is measured. Liver enzymes are correlated with HbA1C values. Results: Among 119 patients, the mean age was 56.65 years. Eighty-three patients (69.7%) were males and 36 (30.3%) were females. The mean duration of diabetes is 8.84±5.81, mean HbA1c is 8.89±2.62. Mean fasting blood sugar and post-prandial blood sugar were 179.4±96.3 and 252±136.5, respectively. There is negative correlation is seen among Aspartate transferase (AST), gamma-glutamyl transferase (GGT) and AST/Platelet (PLT) ratio, but not alanine aminotransferase (ALT). However, there is negative Pearson correlation between HbA1C and liver enzymes as mentioned above which are statistically not significant except AST/PLT ratio. Conclusion: The importance of monitoring the liver function tests in uncontrolled T2DM patients was studied, which showed association among AST, GGT, and AST: ALT ratio with HbA1C. All were negatively correlated with HbA1C, but statistically significant correlation is seen only with AST: PLT ratio.